A Manganese Pre‐Catalyst: Mild Reduction of Amides, Ketones, Aldehydes, and Esters. Issue 50 (15th November 2017) - Kelly, Colin M.; McDonald, Robert; Sydora, Orson L.; Stradiotto, Mark; Turculet, Laura
Abstract: A new ( N ‐phosphinoamidinate)manganese complex is shown to be a useful pre‐catalyst for the hydrosilative reduction of carbonyl compounds, and in most cases at room temperature. The Mn‐catalyzed reduction of tertiary amides to tertiary amines, with a useful scope, is demonstrated for the first time by use of this catalyst, and is competitive with the most effective transition‐metal catalysts known for such transformations. Ketones, aldehydes, and esters were also successfully reduced under mild conditions by using this new Mn catalyst. Abstract : Hey Man(ganese) : A newly prepared ( N ‐phosphinoamidinate)manganese pre‐catalyst (see Scheme) has been shown to be effective for the hydrosilative reduction of a diverse scope of carbonyl compounds, and in most cases can be used at room temperature. The reaction proceeds under reaction conditions that are competitive with the most effective transition‐metal catalysts known for such transformations, and thereby establishes a new class of synthetically useful Mn‐catalyzed transformations.